Econometrics by example - Gujarati, Damodar N (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
"Damodar Gujarati is the author of bestselling econometrics textbooks used around the world. In his latest book, Econometrics by Example, Gujarati presents a unique learning-by-doing approach to the study of econometrics. Rather than relying on complex theoretical discussions and complicated mathematics, this book explains econometrics from a practical point of view, with each chapter anchored in one or two extended real-life examples. The basic theory underlying each topic is covered and an appendix is included on the basic statistical concepts that underlie the material, making Econometrics by Example an ideally flexible and self-contained learning resource for students studying econometrics for the first time. The book includes: - a wide-ranging collection of examples, with data on mortgages, exchange rates, charitable giving, fashion sales and more - a clear, step-by-step writing style that guides you from model formulation, to estimation and hypothesis-testing, through to post-estimation diagnostics - coverage of modern topics such as instrumental variables and panel data - extensive use of Stata and EViews statistical packages with reproductions of the outputs from these packages - an appendix discussing the basic concepts of statistics - end-of-chapter summaries, conclusions and exercises to reinforce your learning - companion website containing PowerPoint slides and a full solutions manual to all exercises for instructors, and downloadable data sets and chapter summaries for students"
-- PART I: THE LINEAR REGRESSION MODEL -- The Linear Regression Model -- Functional Forms of Regression Models -- Qualitative Explanatory Variables Regression Models -- PART II: CRITICAL EVALUATION OF THE CLASSICAL LINEAR REGRESSION MODEL -- Regression Diagnostic I: Multicollinearity -- Regression Diagnostic II: Heteroscedasticity -- Regression Diagnostic III: Autocorrelation -- Regression Diagnostic IV: Model Specification Errors -- PART III: REGRESSION MODELS WITH CROSS-SECTIONAL DATA -- Categorical Dependent Variable Models: The Logit And Probit Models -- Multinomial Regression Models -- Original Regression Models -- Limited Dependent Variable Regression Models -- Modeling Count Data: The Poisson And Negative Binomial Regression Models -- PART IV: TOPICS IN TIME SERIES ECONOMETRICS -- Stationary and Nonstationary Time Series -- Cointegration and Error Correction Models -- Asset Price Volatility: The Arch and Garch Models -- Economic Forecasting with Arima and VAR Models -- Panel Data Regression Models -- Survival Analysis -- Invariables -- Statistical Appendix
Includes bibliographical references and index
Keywords: Econometrics; Regression analysis